(untitled) (European Journal of Engineering Science and Technology, 2022)
A MATLAB model was built for the preparation of initial designs for the establishment of an EAHE system for the purpose of heating and cooling buildings. The purpose of creating this model is to save time and effort by creating a new model capable of providing us and specialized designers with initial perceptions of the size of the appropriate system for the functional requirements for the purpose of cooling and heating buildings. A parametric analysis was then performed to evaluate and investigate the factors affecting the efficiency of the EAHE system. It was found that the pipe diameter is directly proportional to the pipe length, and inversely to the airflow velocity, pressure losses, and AFP. Airflow velocity reduced from 77.05 m/s to 0.1926 m/s, and AFP decreased from 9223 W to 0.058 W when diameter increased from 0.1 m to 2 m. The inlet air temperature affects the length of the pipe in four phases, it is inversely proportional in the first and third phases and directly in the second and fourth phases. These phases depend on the values of soil, inlet, and outlet temperature. This paper presents new equations to determine these phases to determine excluded range which is recommended should not use an inlet air temperature value through this range. The pipe number is directly proportional to pipe length. Pipe length increased from 57.16 m to 344.9 m when the pipe number increased from 1 to 10 pipes. The number of pipes has no influence on the overall airflow velocity or total heat transfer. The length of the pipe is directly proportional to the soil temperature in the first and third phases and inversely proportional in the second and fourth phases. Designers could get an idea of this range by utilizing the equations presented in this paper. There is no direct effect between the soil temperature and power, but rather it affects it through the length of the pipe, as it is directly proportional to pipe length.